2019
DOI: 10.1186/s12933-019-0827-z
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-eluting bioresorbable scaffolds for treatment of coronary artery disease in patients with diabetes mellitus: the midterm follow-up of the prospective ABSORB DM Benelux study

Abstract: Background Percutaneous coronary intervention (PCI) in patients with diabetes mellitus (DM) remains challenging even with modern drug-eluting stents (DES) due to high rates of repeat revascularization. Everolimus-eluting bioresorbable scaffolds (EE-BRS) might allow for repeat intervention prolonging the time interval of percutaneous treatment options. Methods The ABSORB DM Benelux Study is a dedicated prospective, international study to evaluate the midterm safety and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A bioresorbable scaffolds (BRS) may also be an alternative to metallic DES in diabetic patients. A recent study demonstrated the comparable midterm safety and efficacy outcomes of everolimus-eluting BRS in diabetic patients when historically compared with modern DES [41]. Although a concern for the incidence of thrombosis through the process of resorption still exists in the current BRS.…”
Section: Other Devices In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…A bioresorbable scaffolds (BRS) may also be an alternative to metallic DES in diabetic patients. A recent study demonstrated the comparable midterm safety and efficacy outcomes of everolimus-eluting BRS in diabetic patients when historically compared with modern DES [41]. Although a concern for the incidence of thrombosis through the process of resorption still exists in the current BRS.…”
Section: Other Devices In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…Therefore, the “4P technique“ (patient selection, proper sizing, pre-dilatation, and post-dilatation strategy) was proposed for appropriate stent optimization and was an essential part of the BRS implantation procedure in this study. This optimal implantation technique allowed us to partially reset the negative impact of diabetes on patients treated with BRS-ABSORB implantation [ 24 , 25 ]. However, the rate of peri-procedural complications remained higher than that in DES.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, the new generation of drug stents has thinner struts, and better biocompatible polymer coating and newer antiproliferative agents have reduced the rates of cardiovascular events in DM patients with PCI [ 31 ]. Recently, the everolimus-eluting bioresorbable scaffolds treatment in DM patients showed comparable midterm safety and efficacy outcomes when historically compared with modern DES [ 32 ]. In the future, with the development of PCI technology and the renewal of stents, perhaps the gap affected by PCI and CABG in the prognosis of patients with diabetes will be further narrowed.…”
Section: Discussionmentioning
confidence: 99%